Case Report: Anti-mGluR5 antibody-negative Ophelia syndrome with failed lymph node biopsy due to steroid therapy - Sanpei, Yui; Miura, Masahito; Funasaka, Homare; Hanazono, Akira; Kamada, Sachiko; Sugawara, Masashiro (Frontiers in Immunology, 2023)
Ophelia syndrome is paraneoplastic limbic encephalitis (PLE) with Hodgkin lymphoma. Some Ophelia syndrome patients have been reported as testing positive for anti-metabotropic glutamate receptor 5 (mGluR5) antibodies. However, we experienced a case of anti-mGluR5 antibody-negative Ophelia syndrome. The type of onset, neurological symptoms, and imaging as well as electroencephalographic findings were like previous reports except for a normal cell count in cerebrospinal fluid (CSF). Unfortunately, a lymph node biopsy failed and could not diagnose the patient before death because steroid treatment for limbic encephalitis had shrunk lymph nodes. We believe it is essential to accumulate cases of this syndrome and clarify the association between PLE and Hodgkin lymphoma so chemotherapy can be initiated even if malignant lymphoma cannot be pathologically proven or when antibodies cannot be measured or are negative.